Find 2 numbers thats sum to 21 and the sum of squares is 261

Answers

Answer 1
Answer: 15 and 6.

15+ 6 = 21

15^2 + 6^2 = 261

Related Questions

PLEASE HELP SOON. i have been stuck on this algebra 1 question for what feels like an eternity can someone please help and soon?
How do you determine if the line segments are congruent
The total cost C (in dollars) to participate in a ski club is given by the literal equation C=85x+60, where x is the number of ski trips you take.a. Solve the equation for x.b. How many ski trips do you take if you spend a total of $315? $485?
Determine whether the given point lies on the graph of the inequality. (-1,-3); -x-6y < 19. in this case, is the point on the graph (yes or no)
Complete the solution the equation. Find the value of y when x equals 15 .

One time when ms ryland went to the grocery store shee bought all the type of microwave popcorn that the store had with these types of pop corn she conducted an experiment Scientific Question Does the amount of butter on the kernels affect the amount that pop

Give the Independent variable and dependent variable and constants

Answers

Independent variable is what is being changed in the experiment. In this case, the independent variable is the microWave popcorn. Dependent variable is what is being measured. In this case, we are measuring the amount of butter. Constant is what stays the same in the experiment. The constant is same amount of butter, same amount of popcorn , same temperature and so on and so forth.

5/10 + 8/100= ?
13/100, 40/100, 58/100, 6/10

Answers

Answer:

58/100

Step-by-step explanation:

The first step is to make the two fractions have a common denominator. 5/10=50/100. Now you can add the two fractions together. 50/100+8/100=58/100. Hope this helps!

58 / 100 is the answer

W+1/8 =8 plzz help me i need it

Answers

Answer:

w = 7 7/8

Step-by-step explanation:

w + 1/8 = 8

First, subtract 1/8 from both sides of the equation

w + 1/8 = 8

   - 1/8    - 1/8

w = 7 7/8

Answer:

w =  (63)/(8)

alternativeforms:

w= 7 (7)/(8), \: or \: 7.875

step-by-stepexplanation:

w +  (1)/(8)  = 8 \n subtract \:  (1)/(8) \: from \: both \: sides \n  \n w =  (63)/(8)

How does the function f(x) = a ln x compare to the parent function when |a| > 1?

Answers

Answer: The graph is stretched.

Step-by-step explanation:

Answer:

The graph is stretched

Step-by-step explanation:

right on edge 2023

Which of the following is equivalent to the expression below?4x + 3(2x -1) - 4x

Group of answer choices

14x - 3

6x + 3

14x + 3

6x - 3

Answers

Answer:

6x - 3.

Step-by-step explanation:

4x + 3(2x -1) - 4x

= 4x + 6x - 3 - 4x

= 6x - 3.

Final answer:

The correct equivalent expression for 4x + 3(2x -1) - 4x is 6x - 3. This result is achieved by distributing, combining like terms, and simplifying.

Explanation:

The subject of this question is Mathematics, with the problem concerning simplifying expressions in algebra. To handle this problem, first expand the expression 4x + 3(2x -1) - 4x.

From this initial question, follow these steps:

  1. Distribute the 3 in the parenthesis to both the 2x and -1, yielding 3 * 2x and 3 * -1, which are 6x and -3, respectively.
  2. The expression now reads 4x + 6x -3 -4x.
  3. Add the like terms(4x, 6x, and -4x) together: 4x + 6x - 4x = 6x.
  4. The final equivalent expression is 6x - 3.

The correct choice from the given list is therefore 6x - 3, which implies that the equivalent expression for 4x + 3(2x -1) - 4x is 6x - 3.

Learn more about Simplifying Expressions here:

brainly.com/question/36385368

#SPJ2

Y= 6x + 4 and y= 4x - 2

Answers

easy
sub since boht equal y, both are equal
6x+4=y=4x-2
6x+4=4x-2
minus 4x
2x+4=-2
minus 4
2x=-6
divide 2
x=-3
sub back
y=4x-2
y=4(-3)-2
y=-12-2
y=-14

solution in (x,y) form is
(-3,-14)
matrix or it can be y=4